Detection of petrochemicals using photonic crystal fiber (PCF) in terahertz domain - Md. Anowar Kabir; Md. Selim Hossain; Ashik Muhammed Arman; Md. Al-Amin; Shuvo Sen (Sensing and Bio-Sensing Research)
A photonic crystal fiber (PCF) with a hexahedron core has been introduced for usage in petrochemical sensing operations. The performance of the proposed sensor has been statistically analyzed in the frequency band of 1.0 to 3.0 THz. Pure petrol, kerosene, and diesel are poured into the hexahedron core hole. The Finite element Method (FEM) is handled for the simulation and precise calculation and investigation. The sensor utilizing PCF exhibits a relative sensitivity of about 97.80 %, 97.45 %, and 96.25 % and a confinement loss of approximately 1.88 × 10−8 dB/m, 1.90 × 10−8 dB/m, and 1.85 × 10−8 dB/m at 2.20 THz for all investigated Petrol, Kerosene, and Diesel petrochemicals. Moreover, effective areas are values of 7.75 × 10−8 m2, 7.80 × 10−8 m2, and 6.98 × 10−8 m2, and the effective material loss for Petrol, Kerosene, and Diesel of 0.0066168 cm−1, 0.0066955 cm−1 and 0.0066988 cm−1, respectively at 2.20 THz. Both 3D printing and extrusion can be used to create this photonic crystal fiber (PCF) sensor. In addition, this heptagonal photonic crystal fiber sensor will be used for biomedical sensing and various industry fields related to sensing sectors.